Comparing human T cell and NK cell responses in viral-based malaria vaccine trials. - Berthoud, T; Fletcher, H; Porter, D; Thompson, F; Hill, A; Todryk, S (2009)
Vaccination with viral-based vaccines continues to hold promise for the prevention of malaria. Whilst antigen-specific T cell responses are considered a major aim of such an approach, a role for induced NK cells as anti-malarial effector cells, or in shaping T cell responses, has received less attention. In this study naïve human volunteers were vaccinated in a prime-boost vaccination regimen comprising recombinant viral vectors fowlpox (FP9) and modified vaccinia Ankara (MVA) encoding liver-stage antigens, or a virosome vaccine. Significant T cell responses specific for the vectored vaccine antigens were demonstrated by IFNgamma ELISPOT and intracellular cytokine staining (ICS) for IFNgamma and IL-2, the ICS being associated with increased time to parasitaemia following subsequent challenge. Numbers of CD56(bright) lymphocytes increased significantly following vaccination, as did CD3(+) CD56(+) lymphocytes, whilst CD56(dim) cells did not. No such increases were seen with the virosome vaccine. There was no significant correlation of these CD56(+) populations with the antigen-specific T cell responses nor time to parasitaemia. To investigate pathways of immune activation that could contribute to these lymphocyte responses, viral vectors were shown in vitro to efficiently infect APCs but not lymphocytes, and stimulated inflammatory cytokines such as type I interferons. In conclusion, measuring antigen-specific T cells is more meaningful than NK cells in these vaccination regimens.